The Effect of Burning Time on the Yield and Quality of Liquid Smoke from Sengon Wood Waste (Falcataria moluccana) - Muhamad Indra Nurzaman; Andi Tri Lestari; Dini Lestari (Masyarakat Peneliti Kayu Indonesia, 2025)
This study aims to determine the effect of burning time on the yield and quality of liquid smoke produced from sengon wood waste (Falcataria moluccana). The research method employed was an experimental design with a completely randomized design (CRD), consisting of three pyrolysis time treatments: 90 minutes, 120 minutes, and 150 minutes, each with three replicates. The parameters observed included yield, color, floating material, pH, phenol content, acetic acid content, and specific gravity. The results showed that the duration of combustion had a significant effect on the yield and acetic acid content of the liquid smoke, but no significant effect on pH, phenol content, and specific gravity. The highest yield was obtained at a combustion time of 150 minutes, with an average value of 23.07%, while the lowest yield was obtained at 90 minutes, with an average value of 15.90%. The pH value of the liquid smoke ranged from 3.07 to 3.16 and was classified as quality category II based on SNI 8985:2021. The phenol content exceeded the standard limit, while the acetic acid content and specific gravity mostly met the requirements of quality category II.